Monitoring Subcontracting in a Suppliers` Hierachy - Cella, M (Department of Economics (University of Oxford), 2005)
In this paper we study the delegation of a production process in a three-tier hierarchy. The principal contracts directly only with the supplier that produces the …rst input leaving him in charge of the contract for the production of the second input. We allow the principal to costlessly monitor the communication between the agents at the subcontracting stage in an attempt to save on informa- tional rents and improve productive e¢ ciency. We show that, if the contractor is free to choose the type of subcontract, he must be given additional incen- tives to acquire information about the subcontractor which will then be object of the monitoring. The monitoring is therefore much less e¤ective then when the principal can force the contractor into choosing her preferred subcontract.